Traumatic cervical spinal cord injury in southeastern Norway: acute treatment, specialized rehabilitation referral and mortality - Brommeland, Tor; Strøm, Mona; Mirzamohammadi, Jalal; Glott, Thomas; Linnerud, Hege; Rønning, Pål Andre; Rizvi, Syed Ali Mujtaba; Holla, Torjus Mogstad; Høydal, Birgitte Jensen; Biernat, Donata; Aarhus, Mads; Helseth, Eirik (Frontiers in Neurology, 2024)
BackgroundTraumatic cervical spinal cord injury (cSCI) is a serious condition that requires a multidisciplinary treatment approach involving care at a neurotrauma center (NTC) and specialized rehabilitation. Contemporary population-based studies of cSCI are important for ensuring the quality and planning of health care approaches for these patients.MethodsThis is a population-based cohort study of patients with traumatic cSCI who were admitted to the NTC in Southeast Norway between 2015 and 2022. The main outcome variables were length of stay (LOS), rate of surgical fixation/stabilization, rate of transfer to specialized rehabilitation, and 90-day mortality. Uni-and multivariate binary logistic regression analyses were used to investigate the effect of different covariates on LOS, transfer to specialized rehabilitation and 90-day mortality.ResultsThe median age of the 370 patients admitted to the NTC was 64 years, 75% were males, 40% had severe comorbidities, 45% had multiple injuries, and 67% underwent primary triage at a local hospital (LH). Surgical cervical stabilization/decompression was performed in 78% of the patients. The median LOS at the NTC was 9 days, and increasing LOS was significantly associated with young age, American Spinal Injury Association Impairment Scale (AIS) grade B, surgery and prolonged ventilatory support. Inpatient specialized rehabilitation was provided to 54% of patients. Receiving specialized rehabilitation was associated with younger age, preinjury independent living, more severe cSCI, no need for acute phase tracheostomy, and surgical stabilization/decompression. Only 6% of the octogenarians received specialized rehabilitation. The 90-day mortality rate was 13%, which was associated with older age, preinjury dependent living, more severe cSCI, upper cervical injuries, and days on ventilator and inversely correlated with LOS.ConclusionAdvanced age, especially among octogenarians, was significantly linked to a lack of specialized rehabilitation. Qualified physicians should assess all patients with cSCI for their need of rehabilitation and their potential to benefit from it. If the number of patients who are likely to respond to rehabilitation outnumbers the capacity of the rehabilitation center, we have two choices. Either guidelines for prioritization of patients for rehabilitation should be developed, or the capacity of the rehabilitation centers should be increased.